Vasoprotection by Dietary Supplements and Exercise: Role of TNFα Signaling - Zhang, Hanrui (Hindawi Publishing Corporation, 2012)
Vascular dysfunction contributes to the pathogenesis of various cardiovascular diseases. Dietary supplements, including fish oil, dietary fibers, and various natural products, and exercise training exert vasoprotective effects. However, the mechanisms underlying the vasoprotective benefits of dietary supplements and physical activity demand extensive investigation. Accumulating evidence suggests that inflammatory cytokine tumor necrosis factor-alpha (TNFα) plays a pivotal role in the dysregulation of macrovascular and microvascular function. TNFα induces vascular inflammation, monocyte adhesion to endothelial cells, vascular oxidative stress, apoptosis, and atherogenic response and participates in the regulation of thrombosis and coagulation through multiple signaling pathways involving NFκB, Sp1, activator protein 1, JNK, p38, STAT3, and so forth. Dietary supplements and exercise training decrease TNFα production and ameliorate TNFα-mediated pathological changes in vasculature. Thus, the inhibitory effects of dietary supplements and physical exercise on TNFα production and TNFα signaling may contribute to their vasoprotective properties.